Comparison of woody species diversity between managed and unmanaged forests considering vertical structure in Hyrcanian forests, Iran - ZAHRA NOURI; MAHMOUD ZOBEIRI; JAHANGIR FEGHHI; GHAVAMALDIN ZAHEDI AMIRI; MOHAMMAD REZA MARVIE MOHADJER (Society for Indonesian Biodiversity, 2015)
Nouri Z, Zobeiri M, Feghhi J, Amiri GZ, Marvie Mohadjer MR. 2015. Comparison of woody species diversity betweenmanaged and unmanaged forests considering vertical structure in Hyrcanian forests, Iran. Biodiversitas 16: 95-101. Biodiversityconservation is increasingly considered a key to sustainable forest management and understanding biodiversity in forest ecosystems isessential to reveal forest dynamics, so this study aims to compare tree and shrub species diversity and vertical species distributionbetween two managed and unmanaged forest stands. The study area was consisted of two adjacent districts in which two differentmanagement practices were implemented. In 1000 m2 circular plots, type of species and diameter at breast height (D.B.H) of all treeslarger than 2.5 cm as well as type of species of all shrubs and vertical distribution of tree species were recorded. In addition to richness,evenness and heterogeneity indices were calculated for whole tree and shrub species and also for each tree layer. The results showed thattree species diversity indices were significantly greater in the unmanaged area, whereas richness and heterogeneity indices of shrubswere greater in the managed area. Comparing the biodiversity indices indicated that richness index had the greatest value in theunderstorey and heterogeneity indices were greatest in the middle storey in both regions. Greater amounts of evenness were detected inthe middle- and over storey of unmanaged and managed areas, respectively. As forestry operations result in change in various forestcharacteristics such as species diversity, it is essential to assess and monitor the effect of logging operations on forest diversityHyrcanian forests of Iran.